The making of a biathlete: Insights from 2 decades of training data from Junior, World, and Olympic Champions - Kock, H.; Wick, J.; Gronwald, T.; Laaksonen, M. S.; Hanstock, H. (International Journal of Sports Physiology and Performance, 2025)
Aim: To retrospectively describe the annual training characteristics of elite biathletes across different age groups over 2 decades.